Endoscopic submucosal dissection: an update on tools and accessories - Harlow, Christopher (Ther Adv Gastrointest Endosc, 2020)
Endoscopic submucosal dissection (ESD) is a minimally invasive therapeutic procedure to remove larger polyps or early non-metastatic lesions. It has long been used in Asia, but is now fast growing in popularity in the West. There are multiple challenges faced by ESD practitioners. While the practice of ESD in gastric lesions is relatively well established, the oesophagus with its narrow lumen and challenging workspace, and the colon with its tortuous course and folds are more challenging frontiers. The nature of performing a procedure endoscopically means that conventional methods offer no mechanism for providing counter-traction while performing dissection, impeding visibility and increasing the rate of complications. There are a multitude of tools available to those performing ESD for the different stages of the procedure. This article reviews the accessories currently used in regular ESD practice including the knives used to cut and dissect lesions, the cap and hood devices used to improve visibility and safety, injection fluids to lift the submucosal plane, haemostatic devices, generators, and finally, emerging traction apparatus. There is some evidence behind the use of these tools, however, ESD remains the domain of a small number of practitioners and the practice relies heavily on expert experience. Evolution of the ESD toolbox will make the procedure more accessible to more endoscopists, which in turn will drive the development of a more substantial evidence base to evaluate efficacy and safety of the multitude of tools.